Electrodeposited PEDOT:BF4 Coatings Improve Impedance of Chronic Neural Stimulating Probes In Vivo - Jo'Elen Hagler; Jeeyeon Yeu; Xin Zhou; Guillaume Ducharme; Bénédicte Amilhon; Fabio Cicoira (Advanced Materials Interfaces)
Abstract Resulting from its many unique properties, such as mechanical compliancy, electrochemical stability, and high conductivity, the conducting polymer poly(3,4‐ethylenedioxythiophene) (PEDOT) is a promising material for improving the stimulation efficiency of neural microelectrodes. The long‐term electrochemical stability of penetrating PEDOT‐coated electrodes undergoing high‐frequency stimulation is not extensively studied in vivo and the inflammatory response of the brain to PEDOT‐coated stimulating neural probes is not well understood. In this work, electropolymerized PEDOT doped with tetrafluoroborate (PEDOT:BF4) is selectively deposited on the electrode sites of platinum iridium (PtIr) neural probes and implanted for 2 weeks and 2 months to evaluate the effect of implantation on the electrical performance, and the foreign body response to the probes. Histological evaluation after 8 weeks of implantation reveals no difference in the degree of inflammation around PtIr and PEDOT probes. Additionally, PEDOT and PtIr probes are implanted for 60 days, subjected to daily high frequency stimulation and are monitored for changes in electrochemical properties. Impedance measurements reveal an overall lower impedance for PEDOT probes.  These results indicate that PEDOT:BF4 coatings offer a promising approach for improving the stability of neural interfaces for stimulation.